Atomizing core, preparation method thereof and atomizing device
Through the multi-stage sintering process and specific raw material ratio, the problem of short service life of the atomized core is solved, the oil conduction performance of the liquid conduction parts and the connection reliability of the heating parts is improved, the service life of the atomized core is extended and the accumulation is prevented. Carbon and chapped.
Patent Information
- Application Number
- CN202411303768.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-07
AI Technical Summary
The service life of the existing atomized core is short, the oil conduction efficiency of ceramic liquid conduction is not high and it is easy to dry burn and carbon deposits. Microcracks are prone to the connection between the liquid conduction and the heating parts, resulting in a reduced service life.
Using a multi-stage sintering process and specific raw material ratio, anti-cracking agent and hollow glass microbeads are added to reduce the risk of different cracks in sintering cracks and thermal expansion through anti-cracking agents. The hollow glass microbeads improve the oil conduction performance of the liquid conductor and are suitable for Decompose solvents and pore-forming agents at temperatures to prevent cracks caused by rapid decomposition.
It significantly improves the service life of the atomized core, prevents carbon deposits and cracks, and extends the oil conduction performance of the liquid guide and the connection reliability of the heating parts.
Smart Images

Figure CN119263880A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of atomization technology, and in particular to an atomization core and a preparation method thereof, and an atomization device. Background Art
[0002] The atomization device is provided with an atomization core, and the atomization core is used to heat the atomization matrix to generate an aerosol. The atomization core includes a liquid guide and a heating element. The liquid guide transfers the atomization matrix to the heating element, and the heating element heats the atomization matrix to atomize it. The material of the liquid guide can be fiber cotton or ceramic. In the related art, the oil guide efficiency of the ceramic liquid guide is not high, which causes the atomization core to dry burn and produce carbon deposits and block the holes, reducing the service life of the atomization core; in addition, micro cracks are prone to appear at the connection between the liquid guide and the heating element, causing the heating element to fall off, which also reduces the service life of the atomization core. Summary of the invention
[0003] The present application provides an atomizer core and a preparation method thereof, and an atomizer device, which can solve the technical problem of a short service life of the atomizer core.
[0004] In order to solve the above-mentioned technical problems, the present application provides, on the one hand, a method for preparing an atomizer core, comprising: mixing raw materials with a solvent to obtain a ceramic slurry, wherein the raw materials include aggregate, glass powder, pore-forming agent, anti-cracking agent and hollow glass microbeads; forming the ceramic slurry into a liquid-conducting part blank, and embedding a heating part with the liquid-conducting part blank to obtain an atomizer core blank; and performing multi-stage sintering on the atomizer core blank under preset heating conditions to obtain an atomizer core, wherein the atomizer core includes a heating part and a liquid-conducting part, and the liquid-conducting part is sintered by the liquid-conducting part blank.
[0005] In one embodiment, the anti-cracking agent includes silicon dioxide and aluminosilicate, and the anti-cracking agent is prepared by a high temperature treatment process.
[0006] In one embodiment, the hollow glass microspheres include silicon dioxide, boron oxide, and alkali metal oxides. The thermal conductivity of the hollow glass microspheres is 0.038W / m·k-0.085W / m·k, and the density is 0.12g / cm 3 -1.6g / cm 3 .
[0007] In one embodiment, the atomizer core blank is subjected to multi-stage sintering under preset conditions to obtain the atomizer core, including: heating to a first sintering temperature of 140°C-160°C at a first heating rate of 145°C / h-155°C / h, and keeping warm for 1.5h-2.5h; heating to a second sintering temperature of 340°C-360°C at a second heating rate of 170°C / h-190°C / h, and keeping warm for 1.5h-2.5h; heating to a third sintering temperature of 440°C-450°C at a third heating rate of 155°C / h-165°C / h, and keeping warm for 1.5h-2.5h; heating to a fourth sintering temperature of 680°C-720°C at a fourth heating rate of 95°C / h-105°C / h, and keeping warm for 1.5h-2.5h.
[0008] In one embodiment, the raw materials include, by weight: 45-65 parts of aggregate, 15-30 parts of glass powder, 10-25 parts of pore former, 3-10 parts of anti-cracking agent and 3-10 parts of hollow glass microspheres.
[0009] In one embodiment, the aggregate includes one or both of quartz sand and diatomaceous earth; and / or the pore-forming agent includes one or both of polystyrene microspheres and polymethyl methacrylate microspheres; and / or the solvent includes one or both of paraffin and stearic acid.
[0010] In one embodiment, the aggregate includes quartz sand, the median particle size of the quartz sand is 45 μm-55 μm, the median particle size of the glass powder is 45 μm-55 μm, and the median particle size of the pore former is 45 μm-95 μm.
[0011] In one embodiment, the molding conditions of the liquid guide blank include a molding temperature of 60° C.-80° C. and an air pressure of 0.5 MPa-0.7 MPa.
[0012] On the other hand, the present application provides an atomizer core, which is prepared by the preparation method as described above.
[0013] The present application also provides an atomization device, which includes the atomization core as described above, and the atomization core is used to heat the atomization matrix under the action of electricity to atomize it.
[0014] The preparation method provided in the present application comprises the following steps: adding an anti-cracking agent and hollow glass microspheres to the raw materials and adopting a multi-stage sintering process. On the one hand, the anti-cracking agent can reduce the cracks of the ceramic during the sintering process, and reduce the risk of cracking caused by the difference in thermal expansion coefficients between the heating element and the liquid guide element during the use of the atomizer core, thereby increasing the service life of the atomizer core; on the other hand, a part of the spherical shape of the hollow glass microspheres is not completely destroyed after sintering, thereby increasing the oil conduction performance of the liquid guide element, preventing the core from being stuck and carbon deposited, and increasing the service life of the atomizer core; in addition, through multi-stage sintering, the solvent and the pore-forming agent can be gradually decomposed at a suitable temperature, thereby preventing cracks caused by the rapid decomposition of a large amount of organic matter, thereby further increasing the service life of the atomizer core. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0016] Figure 1 It is a structural schematic diagram of an embodiment of an atomization device provided by the present application;
[0017] Figure 2 It is a structural schematic diagram of an embodiment of the atomizer core provided by the present application;
[0018] Figure 3 It is a schematic diagram of a process of an embodiment of a method for preparing an atomizer core provided in the present application;
[0019] Figure 4 This is a naked eye observation of the carbon deposition at the end of the atomizer core test in Comparative Example 1;
[0020] Figure 5 This is a naked eye observation of the carbon deposition at the end of the atomizer core test in Example 1;
[0021] Figure 6 This is a microscopic observation of the carbon deposition of the atomizer core at the end of the test in Example 2;
[0022] Figure 7 This is a microscope observation of the connection between the liquid guide and the heating element when the atomizer core test in Example 2 is terminated. DETAILED DESCRIPTION
[0023] The present application is further described in detail below in conjunction with the accompanying drawings and examples. It is particularly noted that the following examples are only used to illustrate the present application, but are not intended to limit the scope of the present application. Similarly, the following examples are only some embodiments of the present application rather than all embodiments, and all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0024] In the description of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically limited. The terms "first", "second", and "third" in the embodiments of the present application are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first", "second", and "third" can expressly or implicitly include at least one of the features. In the embodiments of the present application, all directional indications (such as up, down, left, right, front, back...) are only used to explain the relative position relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication also changes accordingly. The terms "including" and "having" in the embodiments of the present application and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but optionally also includes steps or units that are not listed, or optionally also includes other steps or components inherent to these processes, methods, products, or devices.
[0025] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0026] This application provides an atomization device. Figure 1 , Figure 2 , the atomizing device 100 may include an atomizer 10. The atomizer 10 stores an atomizing matrix, and the atomizer 10 may atomize the atomizing matrix into an aerosol. The atomizer 10 may include an atomizing core 11 and an oil cup (not shown in the figure). The oil cup is used to store the atomizing matrix, and the atomizing core 11 is installed in the oil cup. The atomizing core 11 is used to heat the atomizing matrix under the action of electricity to atomize it.
[0027] Please continue reading Figure 1 , Figure 2, the atomizing device 100 may also include an atomizing host 20, and the atomizer 10 is electrically connected to the atomizing host 20. The atomizing host 20 may include a battery (not shown in the figure) and a control circuit board (not shown in the figure), so that the atomizing host 20 can control the working state of the atomizer 10. For example, the atomizing host 20 can control the atomizer 10 to heat the atomizing matrix to generate an aerosol or stop heating according to the user's suction action. The atomizer 10 and the atomizing host 20 may be fixedly connected or detachably connected. When the atomizer 10 and the atomizing host 20 are detachably connected, if the remaining amount of the atomizing matrix in the atomizer 10 is less than the preset value, the user can easily separate the atomizer 10 from the atomizing host 20, and the atomizing device 100 continues to be used after the atomizer 10 is replaced, so that the atomizing host 20 can be used multiple times, thereby reducing the user's use cost.
[0028] See also Figure 2 , the atomizing core 11 may include a heating element 111 and a liquid guiding element 112, and the heating element 111 is connected to the liquid guiding element 112. The material of the liquid guiding element 112 may be porous ceramic, and the liquid guiding element 112 may adsorb the atomized matrix and transfer the atomized matrix to the heating element 111. The material of the heating element 111 may be metal, and the function of the heating element 111 is to generate heat by electricity, thereby heating the atomized matrix to atomize it. The liquid guiding element 112 may be in the shape of a hollow cylinder, and the heating element 111 may be in the shape of a hollow grid or spiral. The heating element 111 is accommodated in the liquid guiding element 112, and the heating element 111 is connected to the inner wall of the liquid guiding element 112. The liquid guiding element 112 may also be in the shape of a block, and the heating element 111 may be in the shape of a sheet or a strip, and the heating element 111 is embedded or attached to one side of the liquid guiding element 112. The heating element 111 is connected to the liquid guiding element 112 , so that the heating element 111 and the liquid guiding element 112 form a relatively independent module, which is convenient for modular assembly of the atomizer core 11 and can improve production efficiency.
[0029] This application provides a method for preparing an atomizer core. Figure 3 The method for preparing the atomizer core may include steps S10-S30:
[0030] S10, mixing raw materials with solvent to obtain ceramic slurry, wherein the raw materials include aggregate, glass powder, pore former, anti-cracking agent and hollow glass microspheres. Exemplarily, the mixing and kneading can be carried out in an internal mixer.
[0031] The aggregate has high mechanical strength after sintering, which can provide support for the heating element. Glass powder can enhance the bonding strength between aggregates, making the atomizer core less likely to fall off. The pore-forming agent can decompose during the sintering process, thereby forming pores inside the liquid guide, so that the liquid guide has better oil storage and oil locking capabilities. The anti-cracking agent is used to improve the shrinkage stress impact caused by the cooling and solidification of high-temperature liquid phase materials, reduce the cracks of ceramics during the sintering process; and increase the thermal expansion coefficient of ceramics, thereby reducing the risk of cracking caused by the difference in thermal expansion coefficients between the heating element and the liquid guide during the use of the atomizer core, making the heating element less likely to fall off, and can increase the service life of the atomizer core. Hollow glass microspheres are a hollow spherical powdered inorganic non-metallic material. After sintering, a part of the hollow glass microspheres melts and bonds with the aggregate to form a new aggregate, and a part of the spherical shape is not completely destroyed. The retained part forms a hemispherical or funnel shape, which can improve the oil conduction performance of the liquid guide, prevent carbon accumulation in the core, and increase the service life of the atomizer core.
[0032] S20, forming the ceramic slurry into a liquid guide member blank, and embedding the heating member with the liquid guide member blank to obtain an atomizing core blank.
[0033] A mold can be used in the process of making the atomizer core blank. For example, the heater is first fixed in the mold, and then the ceramic slurry is injected into the mold, so that the ceramic slurry is formed into a liquid guide blank, the heater is embedded in the liquid guide blank, and the heater and the liquid guide blank are embedded to obtain the atomizer core blank; for another example, the ceramic slurry is first injected into the molding barrel to form a liquid guide blank, and then the liquid guide blank is placed in the mold, and the heater is inserted, and the heater is embedded in the inner wall of the liquid guide blank, so that the heater and the liquid guide blank are embedded to obtain the atomizer core blank.
[0034] S30, performing multi-stage sintering on the atomizer core blank under a preset temperature rising condition to obtain an atomizer core, wherein the atomizer core includes a heating element and a liquid guide element, and the liquid guide element is sintered from the liquid guide element blank.
[0035] The atomizer core blank embedded with the heater is sintered to obtain the atomizer core, so that the heater and the liquid guide are integrally formed, and the connection strength between the heater and the liquid guide is high, which can enhance the connection reliability between the heater and the liquid guide. In addition, through multi-stage sintering, the solvent and the pore-forming agent can be gradually decomposed at a suitable temperature, preventing cracks caused by the rapid decomposition of a large amount of organic matter, thereby further improving the service life of the atomizer core.
[0036] The preparation method provided in the present application comprises anti-cracking agent and hollow glass micro-beads added to the raw materials, and a multi-stage sintering process is adopted. On the one hand, the anti-cracking agent can reduce the cracks of the ceramic during the sintering process, and reduce the risk of cracking caused by the difference in thermal expansion coefficient between the heating element and the liquid guide element during the use of the atomizer core, thereby improving the service life of the atomizer core; on the other hand, a part of the spherical shape of the hollow glass micro-beads is not completely destroyed after sintering, which can improve the oil conduction performance of the liquid guide element, prevent the core from being stuck and carbon deposited, and improve the service life of the atomizer core; in addition, through multi-stage sintering, the solvent and the pore-forming agent can be gradually decomposed at a suitable temperature, thereby preventing cracks caused by the rapid decomposition of a large amount of organic matter, thereby further improving the service life of the atomizer core.
[0037] In one embodiment, the ceramic slurry includes 60-80 parts of raw materials and 20-40 parts of solvents by weight. Controlling the weight ratios of raw materials and solvents in the ceramic slurry within the above range can make the fluidity of the ceramic slurry moderate and facilitate molding into a liquid guide blank.
[0038] In one embodiment, the molding conditions of the liquid guide blank include a molding temperature of 60° C.-80° C. and an air pressure of 0.5 MPa-0.7 MPa. By controlling the molding temperature and air pressure, the liquid guide blank can be molded quickly, thereby improving production efficiency.
[0039] In one embodiment, the raw materials include 45-65 parts of aggregate, 15-30 parts of glass powder, 10-25 parts of pore former, 3-10 parts of anti-cracking agent and 3-10 parts of hollow glass microspheres by weight. By controlling the raw material components and ratios, the sintered liquid guide can have suitable mechanical strength, good oil storage and oil locking capabilities, and can increase the service life of the atomizer core.
[0040] In one embodiment, the anti-cracking agent includes silicon dioxide and aluminum silicate, and the anti-cracking agent is prepared by a high-temperature treatment process. Based on the components of the anti-cracking agent, the material structure shape of the anti-cracking agent changes during the sintering process, and the volume increases relatively, thereby improving the shrinkage stress impact caused by the cooling and solidification of the high-temperature liquid phase material; in addition, the aluminum silicate in the anti-cracking agent can increase the thermal expansion coefficient of the ceramic, thereby reducing the risk of cracking caused by the difference in thermal expansion coefficient between the heating element and the liquid guide during the use of the atomizer core. Silica and aluminum silicate are treated at high temperature to enhance the structural stability, and the nucleating agent can still maintain good performance under high temperature conditions; the use of these nucleating agents can effectively refine the grains, improve the strength and toughness of the material, and reduce the generation of defects; in addition, the introduced aluminum element partially improves the heat dissipation performance of the liquid guide and reduces the carbon deposition effect.
[0041] In one embodiment, the main components of the anti-cracking agent include, by mass percentage, 45%-55% O element, 40%-50% Si element, 0.1%-6% Al element, and less than 1% Na, K, and Ca elements.
[0042] In one embodiment, the hollow glass microspheres include silicon dioxide, boron oxide, and alkali metal oxides. The thermal conductivity of the hollow glass microspheres is 0.038W / m·k-0.085W / m·k, and the density is 0.12g / cm 3 -1.6g / cm 3 Based on the hollow glass microsphere components, the hollow glass microspheres have the characteristics of light weight, large volume and low thermal conductivity, thereby reducing the complete destruction of the spherical shape during the sintering process, and the retained part forms a hemispherical or funnel shape, which can improve the oil conduction performance of the liquid guide, prevent the core from sticking and carbon deposition, and increase the service life of the atomizer core.
[0043] In one embodiment, the main components of the hollow glass microspheres include, by mass percentage, 2%-6% B element, 40%-60% O element, 5%-10% Na element, 25%-40% Si element, 2%-7% Ca element, and 0.1%-4% Zn element.
[0044] In one embodiment, the aggregate includes one or both of quartz sand and diatomaceous earth. In one embodiment, the pore former includes one or both of polystyrene microspheres and polymethyl methacrylate microspheres. In one embodiment, the solvent includes one or both of paraffin and stearic acid. Based on the above-mentioned aggregate, pore former and solvent, the sintering temperature of the atomizer core blank can be made relatively low, thereby preventing the heating element from being oxidized during the sintering process.
[0045] In one embodiment, the median particle size of the quartz sand is 45 μm-55 μm, the median particle size of the glass powder is 45 μm-55 μm, and the median particle size of the pore former is 45 μm-95 μm. By controlling the pore size of the raw materials, the consistency of the raw materials can be ensured, thereby making the taste consistency of the atomizer core good.
[0046] In step S30, the atomizer core blank may be sintered in two stages, three stages or more stages, so that the solvent and the pore-forming agent can be gradually decomposed at a suitable temperature to prevent cracks caused by rapid decomposition of a large amount of organic matter. In one embodiment, the atomizer core blank is sintered in four stages, and the atomizer core blank is sintered in multiple stages in sequence under a preset heating condition to obtain an atomizer core, including:
[0047] Raise the temperature to a first sintering temperature of 140°C-160°C at a first heating rate of 145°C / h-155°C / h, and keep the temperature for 1.5h-2.5h;
[0048] Raise the temperature to a second sintering temperature of 340°C-360°C at a second heating rate of 170°C / h-190°C / h, and keep the temperature for 1.5h-2.5h;
[0049] Raise the temperature to a third sintering temperature of 440°C-450°C at a third heating rate of 155°C / h-165°C / h, and keep the temperature for 1.5h-2.5h;
[0050] The temperature is increased to a fourth sintering temperature of 680° C.-720° C. at a fourth heating rate of 95° C. / h-105° C. / h, and kept at this temperature for 1.5 h-2.5 h.
[0051] Generally speaking, the melting point of the solvent (such as paraffin, stearic acid) is lower than that of the pore former. For example, the melting point of the solvent is less than or equal to 100 degrees Celsius, and the melting point of the pore former is greater than or equal to 150 degrees Celsius. The first heating rate is 145°C / h-155°C / h to the first sintering temperature of 140°C-160°C, so that the solvent can be gradually decomposed before the pore former in the first stage; then the second heating rate is 170°C / h-190°C / h to the second sintering temperature of 340°C-360°C, so that the pore former can be gradually decomposed before the pore former in the second stage, that is, the solvent and the pore former can be gradually decomposed at appropriate temperatures respectively, to prevent cracks caused by the rapid decomposition of a large amount of organic matter. Controlling the fourth sintering temperature at 680°C-720°C can make the sintering temperature of the atomizer core blank relatively low, thereby preventing the heating element from being oxidized during the sintering process.
[0052] The present application is described below through specific examples, in which oral products are prepared according to the above preparation method. The following examples are only partial examples of the present application and are not intended to limit the present application.
[0053] Example 1
[0054] According to the mass proportion, 8 parts of diatomaceous earth, 40 parts of quartz sand, 22 parts of glass powder, 18 parts of polystyrene microspheres, 6 parts of hollow glass microspheres, and 6 parts of anti-cracking agent were weighed, wherein the D50 particle size of the quartz sand was 50 μm, the D50 of the glass powder was 50 μm, the D50 particle size of the polystyrene microspheres was 50 μm, the solvent was 90 parts of paraffin and 10 parts of stearic acid, and the materials were mixed and kneaded in a ratio of 7:3 to obtain a ceramic slurry.
[0055] Pour the ceramic slurry into the molding barrel, set the molding temperature to 70°C, the air pressure to 0.6MPa, put the liquid guide blank into the mold, and insert the heating element to complete the integral molding of the liquid guide blank and the heating element. The obtained atomizer core blank is heated to 150°C at a heating rate of 150°C / h, kept warm for 2h, then heated to 350°C at a heating rate of 180°C / h, kept warm for 2h, then heated to 450°C at a heating rate of 160°C / h, kept warm for 2h, and finally heated to 700°C at a heating rate of 100°C / h, and kept warm for 2h. After the obtained atomizer core is cleaned and dried, the finished atomizer core is obtained.
[0056] Example 2
[0057] According to the mass proportion, 8 parts of diatomaceous earth, 40 parts of quartz sand, 22 parts of glass powder, 18 parts of polymethyl methacrylate microspheres, 6 parts of hollow glass microspheres, and 6 parts of anti-cracking agent were weighed, wherein the D50 particle size of the quartz sand was 50 μm, the D50 of the glass powder was 50 μm, the D50 particle size of the polymethyl methacrylate microspheres was 85 μm, the solvent was 90 parts of paraffin and 10 parts of stearic acid, and the materials were mixed and kneaded in a ratio of 7:3 to obtain a ceramic slurry.
[0058] Pour the ceramic slurry into the molding barrel, set the molding temperature to 70°C, the air pressure to 0.6MPa, put the liquid guide blank into the mold, and insert the heating element to complete the integral molding of the liquid guide blank and the heating element. The obtained atomizer core blank is heated to 150°C at a heating rate of 150°C / h, kept warm for 2h, then heated to 350°C at a heating rate of 180°C / h, kept warm for 2h, then heated to 450°C at a heating rate of 160°C / h, kept warm for 2h, and finally heated to 700°C at a heating rate of 100°C / h, and kept warm for 2h. After the obtained atomizer core is cleaned and dried, the finished atomizer core is obtained.
[0059] Comparative Example 1
[0060] According to the mass fraction, 57 parts of quartz sand, 22 parts of glass powder, 15 parts of polystyrene microspheres, and 6 parts of sintering aids are weighed, wherein the D50 particle size of the quartz sand is 50 μm, the D50 of the glass powder is 3 μm, and the D50 particle size of the polystyrene microspheres is 50 μm. The sintering aid can be one or more of kaolin, wollastonite, vermiculite powder, alumina, spodumene, medical stone, and feldspar, and its function is to assist in regulating sintering. The solvent is 90 parts of paraffin wax and 10 parts of stearic acid, and the ceramic slurry is obtained by mixing and kneading according to a ratio of 7:3.
[0061] Pour the ceramic slurry into the molding barrel, set the molding temperature to 70°C, the air pressure to 0.6MPa, put the liquid guide blank into the mold, and insert the heating element to complete the integral molding of the liquid guide blank and the heating element. The obtained atomizer core blank is heated to 150°C at a heating rate of 150°C / h, kept warm for 2h, then heated to 350°C at a heating rate of 180°C / h, kept warm for 2h, then heated to 450°C at a heating rate of 160°C / h, kept warm for 2h, and finally heated to 700°C at a heating rate of 100°C / h, and kept warm for 2h. After the obtained atomizer core is cleaned and dried, the finished atomizer core is obtained.
[0062] Comparative Example 2
[0063] According to the mass fraction, 57 parts of quartz sand, 22 parts of glass powder, 15 parts of polystyrene microspheres, and 6 parts of sintering aids are weighed, wherein the D50 particle size of the quartz sand is 50 μm, the D50 of the glass powder is 3 μm, and the D50 particle size of the polystyrene microspheres is 90 μm. The sintering aid can be one or more of kaolin, wollastonite, vermiculite powder, alumina, spodumene, medical stone, and feldspar, and its function is to assist in regulating sintering. The solvent is 90 parts of paraffin wax and 10 parts of stearic acid, and the ceramic slurry is obtained by mixing and kneading according to a ratio of 7:3.
[0064] Pour the ceramic slurry into the molding barrel, set the molding temperature to 70°C, the air pressure to 0.6MPa, put the liquid guide blank into the mold, and insert the heating element to complete the integral molding of the liquid guide blank and the heating element. The obtained atomizer core blank is heated to 150°C at a heating rate of 150°C / h, kept warm for 2h, then heated to 350°C at a heating rate of 180°C / h, kept warm for 2h, then heated to 450°C at a heating rate of 160°C / h, kept warm for 2h, and finally heated to 700°C at a heating rate of 100°C / h, and kept warm for 2h. After the obtained atomizer core is cleaned and dried, the finished atomizer core is obtained.
[0065] Comparative Example 3
[0066] According to the mass proportion, 17 parts of diatomaceous earth, 40 parts of quartz sand, 22 parts of glass powder, 15 parts of polystyrene microspheres, and 6 parts of hollow glass microspheres were weighed, wherein the D50 particle size of the quartz sand was 50 μm, the D50 of the glass powder was 50 μm, the D50 particle size of the polystyrene microspheres was 50 μm, and the solvent was 90 parts of paraffin and 10 parts of stearic acid. The materials were mixed and kneaded in a ratio of 7:3 to obtain a ceramic slurry.
[0067] Pour the ceramic slurry into the molding barrel, set the molding temperature to 70°C, the air pressure to 0.6MPa, put the liquid guide blank into the mold, and insert the heating element to complete the integral molding of the liquid guide blank and the heating element. The obtained atomizer core blank is heated to 150°C at a heating rate of 150°C / h, kept warm for 2h, then heated to 350°C at a heating rate of 180°C / h, kept warm for 2h, then heated to 450°C at a heating rate of 160°C / h, kept warm for 2h, and finally heated to 700°C at a heating rate of 100°C / h, and kept warm for 2h. After the obtained atomizer core is cleaned and dried, the finished atomizer core is obtained.
[0068] Comparative Example 4
[0069] According to the mass proportion, 14 parts of diatomaceous earth, 40 parts of quartz sand, 22 parts of glass powder, 18 parts of polystyrene microspheres, and 6 parts of anti-cracking agent were weighed, wherein the D50 particle size of the quartz sand was 50 μm, the D50 of the glass powder was 50 μm, the D50 particle size of the polystyrene microspheres was 50 μm, the solvent was 90 parts of paraffin and 10 parts of stearic acid, and the materials were mixed and kneaded in a ratio of 7:3 to obtain a ceramic slurry.
[0070] Pour the ceramic slurry into the molding barrel, set the molding temperature to 70°C, the air pressure to 0.6MPa, put the liquid guide blank into the mold, and insert the heating element to complete the integral molding of the liquid guide blank and the heating element. The obtained atomizer core blank is heated to 150°C at a heating rate of 150°C / h, kept warm for 2h, then heated to 350°C at a heating rate of 180°C / h, kept warm for 2h, then heated to 450°C at a heating rate of 160°C / h, kept warm for 2h, and finally heated to 700°C at a heating rate of 100°C / h, and kept warm for 2h. After the obtained atomizer core is cleaned and dried, the finished atomizer core is obtained.
[0071] The atomizer cores prepared in the examples and comparative examples were tested for oil holding rate, porosity and lifespan.
[0072] Among them, oil holding rate = (unit weight after oil absorption - unit weight before oil absorption) / unit weight after oil absorption; the solvent used is PG:VG = 1:1, the ambient temperature is 25±1°C, and the humidity is 55-75%.
[0073] The porosity test adopts the water saturation method, which is to immerse the sample in water until water no longer penetrates the sample, measure the dry weight and saturated weight of the sample, and calculate the pore volume using the density of water.
[0074] The life test adopts the method of draw 2 and stop 10, in the open oil filling atomizer, 2mL of oil is filled each time, and the inhalation is manually evaluated after filling. The test is terminated when there is a burnt smell or the aerosol concentration is lower than 70%. The test results are shown in Table 1 and Figure 4-Figure 7 shown.
[0075] Table 1 Test results
[0076]
[0077]
[0078] The test results show that in the comparative examples, when no anti-cracking agent and hollow glass microspheres are added to the raw materials (Comparative Example 1, Comparative Example 2) or only one of the anti-cracking agent (Comparative Example 4) or hollow glass microspheres (Comparative Example 3) is added, carbon deposition on the inner wall of the liquid guide is serious ( Figure 4 ), the atomizer core fails due to carbon deposition on the liquid guide, and the life of the atomizer core is about 4,000 puffs; in the embodiment, by adding anti-cracking agent and hollow glass microspheres to the raw materials, the maximum life can reach 12,000 puffs, which is 1-2 times that of the comparative example. Figure 5 It can be seen that when the atomizer core fails at 7900 puffs, there is no carbon deposit on the inner wall of the liquid guide, and the failure reason is that the resistance of the heating element becomes larger. Figure 6 It can be seen that when the atomizer core fails after 12,000 puffs, the carbon deposits on the inner wall of the liquid guide are mainly composed of small particles in the micron size. Although the carbon deposits cannot be completely eliminated, the trend of carbon deposits can be delayed. Figure 7 It can be seen that at the connection between the heating element and the liquid guiding element, after the heating element is peeled off, the porous morphology of the liquid guiding element is obviously distributed, and no obvious cracks are found in the liquid guiding element.
[0079] The above descriptions are only some embodiments of the present application, and do not limit the protection scope of the present application. Any equivalent device or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing an atomizer core, characterized in that: include: Mixing raw materials with a solvent to obtain a ceramic slurry, wherein the raw materials include aggregate, glass powder, pore former, anti-cracking agent and hollow glass microspheres; The ceramic slurry is formed into a liquid guide body, and a heating element is embedded in the liquid guide body to obtain an atomizer core body; The atomizer core is obtained by sintering the atomizer core blank in multiple stages under a preset temperature rising condition, wherein the atomizer core includes the heating element and a liquid guide element, and the liquid guide element is sintered by the liquid guide element blank.
2. The method for preparing the atomizer core according to claim 1, characterized in that: The anti-cracking agent comprises silicon dioxide and aluminosilicate, and the anti-cracking agent is prepared by a high-temperature treatment process.
3. The method for preparing the atomizer core according to claim 1, characterized in that: The hollow glass microspheres include silicon dioxide, boron oxide and alkali metal oxides. The thermal conductivity of the hollow glass microspheres is 0.038W / m·k-0.085W / m·k and the density is 0.12g / cm 3 -1.6g / cm 3 .
4. The method for preparing the atomizer core according to claim 1, characterized in that: The step of sintering the atomizer core blank in multiple stages under preset conditions to obtain the atomizer core comprises: Raise the temperature to a first sintering temperature of 140°C-160°C at a first heating rate of 145°C / h-155°C / h, and keep the temperature for 1.5h-2.5h; Raise the temperature to a second sintering temperature of 340°C-360°C at a second heating rate of 170°C / h-190°C / h, and keep the temperature for 1.5h-2.5h; Raise the temperature to a third sintering temperature of 440°C-450°C at a third heating rate of 155°C / h-165°C / h, and keep the temperature for 1.5h-2.5h; The temperature is increased to a fourth sintering temperature of 680° C.-720° C. at a fourth heating rate of 95° C. / h-105° C. / h, and kept at this temperature for 1.5 h-2.5 h.
5. The method for preparing the atomizer core according to claim 1, characterized in that: In terms of mass fraction, the raw materials include: 45-65 parts of aggregate, 15-30 parts of glass powder, 10-25 parts of pore-forming agent, 3-10 parts of anti-cracking agent and 3-10 parts of hollow glass microspheres.
6. The method for preparing the atomizer core according to claim 1, characterized in that: The aggregate includes one or both of quartz sand and diatomaceous earth; and / or, The pore-forming agent includes one or both of polystyrene microspheres and polymethyl methacrylate microspheres; and / or, The solvent includes one or both of paraffin and stearic acid.
7. The method for preparing the atomizer core according to any one of claims 1 to 6, characterized in that: The aggregate comprises quartz sand, the median particle size of the quartz sand is 45 μm-55 μm, the median particle size of the glass powder is 45 μm-55 μm, and the median particle size of the pore former is 45 μm-95 μm.
8. The method for preparing the atomizer core according to any one of claims 1 to 6, characterized in that: The molding conditions of the liquid-conducting component blank include a molding temperature of 60° C.-80° C. and an air pressure of 0.5 MPa-0.7 MPa.
9. An atomizer core, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. An atomizing device, characterized in that: The atomizer core comprises the atomizer core as claimed in claim 9, wherein the atomizer core is used for heating the atomizer substrate to atomize it under the action of electricity.
Citation Information
Patent Citations
Porous ceramic for electronic cigarette and preparation method thereof
CN111205104A
Porous ceramic as well as preparation method and application thereof
CN117024174A